DINESCAPE, emotions, and behavioral intentions in upscale restaurants - Ryu, Kisang (Kansas State University, 2005)
The physical environment may be an important determinant of customer satisfaction and subsequent behavior when services are consumed primarily for hedonic purposes and customers spend moderate to long periods of time in the physical surroundings. An example of this phenomenon would be in an upscale restaurant setting. This study explored the domain of the physical environment in an upscale restaurant context to develop a DINESCAPE scale. Relevant literature was reviewed on architecture, environmental psychology, psychology, operations management, and marketing, highlighting empirical and theoretical contributions. Conceptualization and operationalization of the DINESCAPE dimensions is presented, and the procedures used in constructing and refining a multiple-item scale to assess DINESCAPE in an upscale restaurant setting are described. DINESCAPE is a six-factor scale that was developed to measure facility aesthetics, ambience, lighting, service product, layout, and social factors. Evidence of the scale’s reliability, validity, and factor structure is presented, along with potential applications of the scale. The second phase of the study attempted to build a conceptual model of how the DINESCAPE factors influenced customers’ behavioral intentions through their emotions. The Mehrabian-Russell environmental psychology model was adopted to explore the linkage of the six dimensions of DINESCAPE to customers’ emotional states (pleasure and arousal) and the linkage between pleasure and arousal with customers’ behavioral intentions. Structural equation modeling was used to test the causal relationships among the hypothesized relationships. Results revealed that facility aesthetics, ambience, and social factors affected the level of customers’ pleasure and ambience and social factors influenced the amount of arousal. In addition, pleasure and arousal had significant effects on subsequent behavioral intentions in the context of upscale restaurant. Finally, implications for restaurateurs and researchers were discussed.
Keywords: Physical environment; DINESCAPE; Emotions; Behavioral intentions; Upscale restaurants; Management (0454)